ANALISIS KUALITAS PELAYANAN SAPAMAS DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KARANGANYAR - Pramesti, Nasya Gita; Suhita, Damayanti; Sugiyarti, Sri Riris (Solidaritas, 2024)
Through the Community Aspiration Networking Information System (SAPAMAS) service, the Karanganyar Regency Communication and Informatics Office manages complaints and aspirations of the Karanganyar Regency community. This study aims to assess the quality of sapamas services provided by the Karanganyar Regency Communication and Informatics Office. A qualitative approach is used in this study by referring to the theory of service quality dimensions according to Parasuraman, Zeithaml, and Berry (in Tjiptono F 2019: 305) including indicators of Tangibel (Physical Evidence), Assurance (Guarantee), Reliability, Responsiveness, and Empathy. The results showed that the quality of sapamas services at the Karanganyar Regency Communication and Information Service can be said to be good. As in the Tangible dimension (Physical Evidence), the appearance of neat and polite officers, a large enough parking area and the availability of a comfortable waiting room. In the Reliability Dimension, officers are careful and able to serve public complaints according to the Sapamas SOP. The Responsiveness dimension of the officer is good in responding to public complaints. The Assurance dimension is that service users are free of charge and are given a guarantee of 3-8 days of complaint resolution time and a maximum of 35 days for complaints that require field inspection. The Empathy dimension is that officers are kind, friendly, polite, patient and prioritise the interests of the community. However, from the 5 dimensions used, there are various things that need to be improved and improved so that service users are satisfied with the services shared by the Karanganyar Regency Informatics Communication Service, such as the dimensions of Tangible (Physical Evidence), Responsiveness (Responsiveness), For the sake of SAPAMAS service customer satisfaction, there needs to be wider socialisation of current regulations and time guarantees in accordance with the SOP (Standard Operating Procedure). Keywords: Quality, Service, Sapamas